The Relationship Between Parental Attention And Learning Discipline Of Catizens Learning Package B In SPNF SKB Lima Puluh Kota - Khairunnisa, Gisandha; Sunarti, Vevi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The aim of this research is to find out the picture and also the relationship between parental attention and learning discipline at SKB Lima Puluh Kota. This research uses a correlational quantitative approach. The population of this study is all residents studying Package B class 9 of SKB Lima Puluh Kota, namely 40 people who have the characteristics of living with their parents. The sampling technique in this research was carried out using a random sampling method, so the total sample taken by the researchers was 30 people. The data collection technique uses a questionnaire format and a list of statements as a data collection tool, the data analysis technique uses percentages to find correlations using the product moment formula. The results of this research are: 1.) Parents' attention to residents studying package B at SKB Lima Puluh Kota is relatively low, 2.) The educational field of residents enrolled in package B at SKB Lima Puluh Kota is relatively low and 3.) There exists a notable correlation between parental attentiveness and academic discipline at SKB Lima Puluh Kota.Keywords: Attention, Discipline, SPNF SKB.